(untitled) (Economic and Political Thought, 2015)
The paper aims to study the relationship between differences in national innovation capabilities within three sectors, which are the main building blocks of an innovation system, and country variations in GDP per capita. Research in this area has previously focused mostly on the impact of differently defined innovation capabilities on the level of economic development of countries, neglecting innovation system sectors approach. The analysis conducted for this paper has allowed do confirm that there is a positive relationship between country variations in innovation capabilities within two of the sectors: enterprise sector and higher education sector, and national differences in GDP per capita. While the relationship between differences in innovation capabilities within the latter sector is linear in character, the interdependence between country variations in enterprise sector innovation capabilities and economic development are evidently non-linear. Values of composite indexes calculated for the enterprise sector innovation capabilities above a certain level have not been accompanied by corresponding higher values of GDP per capita – this relationship has been evident in both analysed periods. The study based on gathered statistical information has also allowed to conclude that during 10 years between 2002–2003 and 2012–2013 there have not been observed any significant changes on the Europe’s map of innovation leaders.